Magnetic resonance imaging characterisation of lesions within the collateral ligaments of the distal interphalangeal joint – 28 cases. (10th May 2019) - Beasley, B.; Selberg, K.; Giguère, S.; Allen, K.
Summary: Collateral ligament (CL) desmopathy of the distal interphalangeal joint (DIPJ) is a known injury that is not uncommonly diagnosed in horses presenting for lameness isolated to the foot. Ultrasonography and radiography are often used as primary diagnostic tests with mixed success. Medical records of horses undergoing magnetic resonance imaging (MRI) of the foot between November 2007 and October 2015 were reviewed. Horses were included only if the MRI followed an examination that localised a component of the lameness to the foot, and the MRI study indicated that CL desmopathy of the DIPJ was the most important finding. Thirty‐four limbs from 28 horses were included and 48 CL desmopathies were identified. Of the 48; 27 were distal to the coronary band, 15 were proximal to the coronary band, five lesions involved the entire ligament, and one CL had proximal and distal focal lesions. Twenty‐four of the 28 horses were able to return to work. There was no significant association between severity or lesion location and time to return to work. This study confirms that a high proportion of CL lesions of the DIPJ are located distal to the coronary band and require MRI for an accurate diagnosis that would otherwise be missed by ultrasound examination alone.